Diabetes Melitus and Lifestyle Patterns in Society: A Comprehensive Literature Review - Ahmad Syaripudin; Karningsih; Abdul Supardi; Nura Ali Dahbul; Rolly H. S. Rondonuwu (International Journal of Science and Society, 2023)
Diabetes Mellitus, especially type 2 is a disease that is quite deadly. One of the causes of this disease is an unhealthy lifestyle in the community. This study then aims to look at how people's lifestyle patterns can cause diabetes mellitus. This research is qualitative research with a literature review method. The data used in this research comes from various relevant research results and studies. The results of this study then found that eating fast food can increase the sugar and fat content, which then disrupts blood regulation and insulin resistance. Then less physical activity causes the body's sensitivity to insulin to decrease. These things then lead to the development of diabetes mellitus due to an imbalance in insulin production with the body's needs. Therefore, a healthy lifestyle can increase insulin sensitivity and reduce the impact of the risk of diabetes mellitus.